Molecular electrostatic potential and pattern recognition models to design potentially active pentamidine derivatives against Trypanosoma brucei rhodesiense (Research, Society and Development, 2021)
Molecular electrostatic potential (MEP) and pattern recognition (PR) were used to draw potentially active pentamidine derivatives against Trypanosome brucei rhodesiense (T. b. rhodesiense). PR models: Principal Component Analysis, PCA model; Hierarchical Cluster Analysis, HCA model; K-Nearest Neighbor, KNN model; Soft Independent Modeling of Class Analogy, SIMCA model; and Stepwise Discriminant Analysis, SDA model, were built by reducing the dimensionality of a data matrix to twenty-eight pentamidine derivatives and allowed the compounds to be classified into two classes: more active and less active, according to their degrees of activity against T. b. rhodesiense. The study outlined that the properties HOMO (highest occupied molecular orbital) energy, VOL (molecular volume), and ASA_P (water accessible surface area of all polar (½qi½³0. 2) atoms) are the most relevant for the construction of the models. The key structural features required for biological activity investigated through MEP were used as guidelines in the design of thirteen new compounds, which were evaluated by PR models as more active or less active against T. b. rhodesiense. The application of PR models indicated nine promising compounds (29, 30, 31, 32, 33, 36, 37, 39, and 40) for synthesis and biological assays.